High resolution digital 3D modelling of subsurface morphological structures of Koutouki Cave, Greece - Konsolaki, Aliki; Vassilakis, Emmanuel; Gouliotis, Leonidas; Kontostavlos, Georgios; Giannopoulos, Vassilis (Acta Carsologica, 2020)
Remote sensing techniques and laser scanning technology have given us the opportunity to study indoor environments, such as caves, with their complex and unique morphology. In the presented case study, we used a handheld laser scanner for acquiring points with projected coordinate information (X, Y, Z) covering the entire show cave of Koutouki; including its hidden passages and dark corners. The point cloud covers the floor, the walls, and the roof of the cave, as well as the stalactites, stalagmites and the connected columns that constitute the decoration of the cave. The absolute and exact placement of the point cloud within a geographic reference frame gives us the opportunity for three-dimensional measurements and detailed visualization of the subsurface structures. Using open - source software, we managed to make a quantification analysis of the terrain and generated morphological and geometric features of the speleothems. We identified 55 columns by using digital terrain analysis and processed them statistically in order to correlate them to the frame of the cave development. The parameters that derived are the contours, each column height, the speleothem geometry and volume, as well as the volume of the open space cavity. We argue that by the demonstrated methodology, it is possible to identify with high accuracy and detail: the geomorphological features of a cave, an estimate of the speleogenesis, and the ability to monitor the evolution of a karstic system. Key words: cave, laser scanner, 3D representation, speleothems, SLAM.